2013
DOI: 10.2967/jnumed.112.115436
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Suppresses Cancer Cell Glucose Uptake by Targeting Reactive Oxygen Species–Mediated Hypoxia-Inducible Factor-1α Activation

Abstract: Resveratrol is gaining attention for its anticancer effects and is also recognized for its antioxidant properties and influence on glucose metabolism. Augmented reactive oxygen species (ROS) and high glycolytic flux are common characteristics of malignant cells. We thus evaluated the effect of resveratrol on cancer cell glucose metabolism and investigated the role of ROS in the response. Methods: Cancer cells were measured for cell content and 18 F-FDG uptake. Assays were performed for lactate production; hexo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 36 publications
0
86
0
Order By: Relevance
“…A high level of ROS production has also been reported in cancer tissue. Jung et al 31 have reported a positive relationship between the uptake of 18 • − was increased in SOD-deficient mice or ketamine-treated mice. In addition, the product of hydroethidine oxidation produced by O 2…”
Section: In Vitromentioning
confidence: 97%
“…A high level of ROS production has also been reported in cancer tissue. Jung et al 31 have reported a positive relationship between the uptake of 18 • − was increased in SOD-deficient mice or ketamine-treated mice. In addition, the product of hydroethidine oxidation produced by O 2…”
Section: In Vitromentioning
confidence: 97%
“…RSV inhibits also cyclooxygenase activity (Banerjee et al, 2002; Kowalczyk et al, 2010; Li et al, 2002), which has an important role in tumorigenesis. Finally, it suppresses glucose uptake and glycolysis in cancer cells through reduced generation of intracellular reactive oxygen species (ROS) (Jung et al, 2013). …”
Section: General Overview Of the Pleiotropic Effects Of Rsv In In mentioning
confidence: 99%
“…While rotenone and DPI reduced ROS formation in this study, these agents are not likely to be utilized as a form of chemotherapy given their reported toxicity to healthy cells [72,73]. In another study, administration of the antioxidant resveratrol, a plant-based product with cardio-protective and anti-cancer properties, was reported to limit glycolytic metabolism in several cancer cell lines as a result of its down-regulation of intracellular ROS, which resulted in a concomitant decrease in HIF-1α expression [74]. Evaluating the use of antioxidants to limit metastasis, Shimojo et al [58] discovered that administration of the antioxidant n-acetylcysteine (NAC) suppressed markers of EMT in human pancreatic cancer cell lines exposed to hypoxia in-vitro and in-vivo and reduced metastatic spread in xenograft pancreatic cancer-bearing mice.…”
Section: Targeting Ros To Improve Cancer Therapymentioning
confidence: 99%